Pilot study on biocompatibility of fluorescent nanodiamond-(NV)-Z~800 particles in rats: safety, pharmacokinetics, and bio-distribution (part III) - Barone FC (Dove Medical Press, 2018)
Frank C Barone,1 Cezary Marcinkiewicz,2,3 Jie Li,1 Mark Sternberg,3 Peter I Lelkes,2 Dmitriy A Dikin,4 Peter J Bergold,1 Jonathan A Gerstenhaber,2 Giora Feuerstein3 1Department of Neurology, SUNY Downstate Medical Center, Brooklyn, NY, USA; 2Department of Bioengineering, Temple University, College of Engineering, Philadelphia, PA, USA; 3Debina Diagnostics Inc, Newtown Square, PA, USA; 4Department of Mechanical Engineering, Temple University, Philadelphia, PA, USA Introduction: We hereby report on studies aimed to characterize safety, pharmacokinetics, and bio-distribution of fluorescent nanodiamond particles (NV)-Z~800 (FNDP-(NV)) administered to rats by intravenous infusion in a single high dose. Methods: Broad scale biological variables were monitored following acute (90 minutes) and subacute (5 or 14 days) exposure to FNDP-(NV). Primary endpoints included morbidity and mortality, while secondary endpoints focused on hematology and clinical biochemistry biomarkers. Particle distribution (liver, spleen, lung, heart, and kidney) was assessed by whole organ near infrared imaging using an in vivo imaging system. This was validated by the quantification of particles extracted from the same organs and visualized by fluorescent and scanning electron microscopy. FNDP-(NV)-treated rats showed no change in morbidity or mortality and preserved normal motor and sensory function, as assessed by six different tests. Results: Blood cell counts and plasma biochemistry remained normal. The particles were principally distributed in the liver and spleen. The liver particle load accounted for 51%, 24%, and 18% at 90 minutes, 5 days, and 14 days, respectively. A pilot study of particle clearance from blood indicated 50% clearance 33 minutes following the end of particle infusion. Conclusion: We concluded that systemic exposure of rats to a single high dose of FDNP-(NV)-Z~800 (60 mg/kg) appeared to be safe and well tolerated over at least 2 weeks. These data suggest that FNDP-(NV) should proceed to preclinical development in the near future. Keywords: fluorescent nanodiamond particles, biocompatibility, near infrared imaging, scanning electron microscopy, neurobehavioral function, pharmacokinetics, rat